INVESTIGATING PAKISTANI EFL TEACHERS’ ATTITUDE TOWARDS FACE-TO FACE, ONLINE AND BLENDED MODES OF TEACHING: A QUALITATIVE STUDY: Pakistani Teachers' Attitude towards Modes of study - Pervaiz, Beenish (Journal of Peace, Development and Communication, 2022)
This study intends to investigate Pakistani EFL teachers’ attitudes towards face to face, online and blended modes of teaching. The study is qualitative in nature. The data has been collected through semi-structured interview from 20 teachers who were willing to participate in this study and were also having the experience of teaching in face to face, online and blended modes of teaching. The qualitative data collected through semi-structured interview has been analyzed through thematic analysis approach. The emerging themes, the problems being faced by the teachers in face to face teaching mode, were over-crowded classes, prescriptive syllabus, de-motivated students, non-conducive classroom environment and less cooperative management. In online teaching mode, the teachers faced problems such as average or poor computer knowledge, no proper tools for online classes, no positive impact on learning of students, less comfort level while taking online classes, no proper training, and less support and resources from management. The teachers also opine that they have problems in blended mode of teaching as well that are time consuming issue, learning isolation, learners’ frustration, anxiety and confusion, and higher class drop out ratio.